Formation of memorable tourism experience and its influence on destination image-evidences from literature. (2017) - Nair, Vinith Kumar; Raju, M.
Memorable tourism experience is basically about a tourism experience recollected and reviewed after the occasion has happened. It is specifically developed from tourism experiences in the light of the individual's assessment of the experience. There are lots of factor which leads to the formation of a memorable tourism experience. This article focuses on the available evidences from literature about how a memorable tourism experience is formed and what is its influence on destination image.